2020
DOI: 10.3390/min10121056
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Magnetic Analyses for the Discrimination of Urban and Industrial Dusts

Abstract: Industrial and urban dusts were characterized by investigating their magnetic properties. Topsoil composed of technogenic magnetic particles (TMP) originating from areas affected by three ironworks, street dust mainly composed of traffic-related pollution, and particulate matter (PM) from urban agglomeration in Warsaw, Poland were investigated. Several magnetic methods, namely magnetic susceptibility, thermomagnetic curves, hysteresis loops, decomposition of isothermal remanent magnetization acquisition curves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Hematite and magnetite are main magnetic Fe-bearing phases present in the sinter dust sample (Figure 14; Table 4). The observed Mössbauer parameter values for the spectrum of the ferric iron doublet of this sample can be interpreted to be iron-containing glass [45,46]. Mössbauer spectra of the iron-bearing sludge dusts, samples No.…”
Section: Iron-bearing Phase Identificationmentioning
confidence: 76%
See 1 more Smart Citation
“…Hematite and magnetite are main magnetic Fe-bearing phases present in the sinter dust sample (Figure 14; Table 4). The observed Mössbauer parameter values for the spectrum of the ferric iron doublet of this sample can be interpreted to be iron-containing glass [45,46]. Mössbauer spectra of the iron-bearing sludge dusts, samples No.…”
Section: Iron-bearing Phase Identificationmentioning
confidence: 76%
“…Furthermore, two doublets were also observed: the first with IS = 1.03 mm/s and QS = 0.63 mm/s correspond to the presence of Fe 2+ in wüstite, while the second doublet with IS of about 0.19 mm/s and QS = 0.42 mm/s, is assigned to Fe 3+ ions. It might be assumed that this doublet corresponds to iron-containing glass [45,46]. Hematite and magnetite are main magnetic Fe-bearing phases present in the sinter dust sample (Figure 14; Table 4).…”
Section: Iron-bearing Phase Identificationmentioning
confidence: 99%
“…Several studies have shown that both urban and industrial dusts contain significant amounts of solid particles with strong magnetic properties, mainly exhibiting ferromagnetic sensu lato properties, which can be easily detected by magnetic methods, even in small amounts (e.g., Bourliva et al 2017 ; Gonet and Maher 2019 ; Górka-Kostrubiec et al 2020 , 2023 ; Gonet et al 2021 ; Magiera et al 2021 , 2023 ). Therefore, the magnetic properties of dust can be used to quantify magnetic particles and distinguish their source origin.…”
Section: Introductionmentioning
confidence: 99%
“…Foundry dust is considered as the ultimate waste, and the solid materials collected from the gas treatment units before the gases are released into the atmosphere account for the second largest proportion of total waste during the casting process. The common constituent in waste foundry dust (WFD) produced by foundries is iron-containing minerals, primarily consisting of Fe and O in the form of magnetite (Fe 3 O 4 ), owing to the processes depending on reduction/oxidation conditions and rapid cooling after combustion processes [ 7 ]. In addition, in the process of capturing gases, CaO is used to neutralize the acid gas generated under elevated temperatures during the production of casting [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%